Could generative artificial intelligence serve as a psychological counselor? Prospects and limitations - J.A. Teixeira da Silva; Y. Yamada (Central Asian Journal of Medical Hypotheses and Ethics)
Humanity’s ability to embrace artificial intelligence (AI), or the skills and “knowledge” that it can impart, depends not only on the control of input fed to AI, but also on output management. When properly managed, the AI output, including of large language models (LLMs) such as ChatGPT, can complement human endeavor and excellence. Yet, if abused or left to its own computational vices, AI might cause harm to humans and thus humanity. Within this in mind, this perspective paper offers a reflection on whether LLM-based AI, having the capacity to integrate text, voice and speech, could assist in personal or psychological counseling processes. Cognizant that psychological counseling places the human factor as a central premise of therapy, AI could be perceived as a risk of replacing human-centered counseling roles, even though it might provide assistance to humans under strictly controlled conditions. While the replacement of human-based counseling is not being advocated, there is value in considering the possibility of applying LLM-based AI tools as counseling aides, as AI-human teams, under strict human supervision, and following stringent testing, provided that an ethical working framework and reliability in AI performance can be established.